Generation of multiple resonance wavelengths from one dimensional photonic crystal wire for nanoscopic wavelength division multiplexing system - Mohd Nuriman, Nawi (Universiti Malaysia Perlis (UniMAP), 2021)
Link to publisher's homepage at http://ijneam.unimap.edu.my